Health and toxicology - Cheremisinoff, Paul N.; Bacis, M. (Houston, Tex. : Gulf Pub., 1997)
This addition to the Advances in Environmental Control Technology Series contains 23 chapters designed to provide an extensive overview and reference on human physiological responses to various forms of pollution.
Environmental risk factors on cancer and their primary prevention / J.W. Dobrowolski -- Respiratory function changes from inhalation of polluted air / Shieh-Ching Yang and Sze-Piao Yang -- Biological markers of early health effects in the assessment of the risk of cancer in people exposed to environmental carcinogens / Janusz A. Indulski and Waldemar Lutz -- Sick building syndrome / Peter Dingle -- Respiratory findings of construction workers exposed to asbestos dust / Isamu Ebihara ... [et al.] -- Asbestos exposure and the risk of lung cancer in urban populations / Anti Karjalainen and Anttila Sisko -- Emphysema and lung mineral content in coalworkers / J. Leigh, T. Driscoll, and B. Cole -- Sinonasal cancer and wood dust exposure / A. Leclerc and D. Luce -- Chromium accumulation of chromate workers' bronchi / Yuichi Ishikawa and Eiju Tsuchiya -- Benzene toxicokinetics in humans / Frederic Yves Bois -- Fluorometry of carcinogenic polycyclic aromatic hydrocarbons in biological systems / Kuang-Pang Li, Ping Chiang, and Raxia Song -- Occupational exposure to organic solvents during paint stripping and painting / Marc Charretton and Raymond Vincent -- Occupational exposure to metallic cobalt / G. Mosconi ... [et al.] -- Climate and chronic respiratory disease / Paul Beggs and Peter Curson -- Effects of acid precipitation on the environment and on human health / Lars Gerhardsson, Staffan Skerfving and Agneta Oskarsson -- Toxic effect of tannery effluent on the biochemical constituents in organisms / G. Varadaraj and M.A. Subramanian -- Bladder cancer and water disinfection methods / Michael A. McGeehin, John S. Reif -- Metal-induced development toxicity in mammals / Jose L. Domingo -- Genetic evaluation of pesticides in different short-term tests / Patrizia Hrelia -- Pesticide residues in food / Peter Dingle -- Biological monitoring by means of urinary samples and problems concerning concentration-dilution of spot urine / Andrea Trevisan -- Causes of artifacts in sorption studies with trace elements / Lorenzino Giusti -- Bioaccumulation of surfactants / J. Tolls and D.T.H.M. Sijm.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Environmental toxicology; Environmental Pollution -- Αdverse effects; Environmental Pollutants -- toxicity; Electronic books